2014
DOI: 10.1136/thoraxjnl-2014-205213
|View full text |Cite
|
Sign up to set email alerts
|

Viability ofPseudomonas aeruginosain cough aerosols generated by persons with cystic fibrosis

Abstract: BackgroundPerson-to-person transmission of respiratory pathogens, including Pseudomonas aeruginosa, is a challenge facing many cystic fibrosis (CF) centres. Viable P aeruginosa are contained in aerosols produced during coughing, raising the possibility of airborne transmission.MethodsUsing purpose-built equipment, we measured viable P aeruginosa in cough aerosols at 1, 2 and 4 m from the subject (distance) and after allowing aerosols to age for 5, 15 and 45 min in a slowly rotating drum to minimise gravitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
103
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 35 publications
3
103
3
Order By: Relevance
“…The experimental equipment comprised of two validated, independent systems to study the distance travelled and survival duration of bacteria contained in aerosols generated during coughing 5. Participants completed five cough experiments; distance studies involved aerosol sampling at 2 and 4 m, while the duration studies involved the ageing of cough aerosol samples for 5, 15 and 45 min prior to extraction 5.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental equipment comprised of two validated, independent systems to study the distance travelled and survival duration of bacteria contained in aerosols generated during coughing 5. Participants completed five cough experiments; distance studies involved aerosol sampling at 2 and 4 m, while the duration studies involved the ageing of cough aerosol samples for 5, 15 and 45 min prior to extraction 5.…”
Section: Methodsmentioning
confidence: 99%
“…The authors calculated that 90% of viable bacteria would be removed in 50 min at a ventilation rate of two air changes per hour, and in 13 min at 10 air changes per hour. 26 Significant variability was observed in aerosol production between different patients. Cough aerosol quantity correlated with sputum bacterial load.…”
Section: Transmissibility Of Cf Pathogensmentioning
confidence: 97%
“…We previously reported that 8% of air samples obtained z3 feet from participants in CF clinics contained their respiratory tract pathogens (12). Cough aerosols from patients with CF contained infectious droplets within the respirable range that traveled 6-12 feet (13,14). Recently, patient-to-patient transmission of Mycobacterium abscessus occurred in a CF clinic, and airborne transmission was postulated (15).…”
mentioning
confidence: 96%